Zavezujoča narava odločb Ustavnega sodišča - Sovdat, Jadranka (Podjetje in delo, 2015)
The article considers the legally binding nature of the Constitutional Court of the Republic of Slovenia decisions in relation to the legislature and to the (ordinary) courts. It defines the legal effects of the Constitutional Court decisions reviewing the constitutionality of statutes and those resolving constitutional complaints. In addition, the article deals with the manner of execution of Constitutional Court decisions and the legal nature and binding effect of their manner of execution.
Keywords: odločanje; sodne odločbe; ustavna pritožba; ustavna sodišča; ustavnost